Dietary linoleic acid and human health: Focus on cardiovascular and cardiometabolic effects - Marangoni, Franca; Agostoni, Carlo; Borghi, Claudio; Catapano, Alberico L.; Cena, Hellas; Ghiselli, Andrea; La Vecchia, Carlo; Lercker, Giovanni; Manzato, Enzo; Pirillo, Angela; Riccardi, Gabriele; Risé, Patrizia; et al. (Atherosclerosis, 2020)
This narrative review aims to discuss the more relevant evidence on the role of linoleic acid (LA), a n-6 essential fatty acid that constitutes the predominant proportion of dietary polyunsaturated fatty acids (PUFA), in cardiovascular health. Although LA can be metabolized into Arachidonic Acid (AA), a 20 carbon PUFA which is the precursor of eicosanoids, including some with proinflammatory or prothrombotic-vasoconstrictor action, the large majority of experimental and clinical studies have assessed the potential benefit of increasing dietary intake of LA. Overall, data from clinical studies and meta-analyses suggest an association between high dietary intakes or tissue levels of n-6 PUFA, and specifically LA, and the improvement of cardiovascular risk (mainly of the plasma lipid profile), as well as long-term glycaemic control and insulin resistance. Most observational data show that elevated/increased dietary intake or tissue levels of LA is associated with a reduced incidence of cardiovascular diseases (mainly coronary artery diseases) and of new onset metabolic syndrome or type 2 diabetes. The effects of LA (or n-6 PUFA) in other physio-pathological areas are less clear. High quality clinical trials are needed to assess both the actual amplitude and the underlying mechanisms of the health effects related to dietary intake of this essential fatty acid. [Display omitted] •Linoleic acid (LA) is an essential18-carbon n-6 polyunsaturated fatty acid.•An adequate dietary supply of LA is crucial for human health.•LA intakes/blood levels are inversely correlated with cardiovascular disease risk.•LA intakes should be increased in most western countries.